Calibration of the design of cholesterol in order to balance the light of the day with the thermal performance in order to raise the sustainability of university buildings in Syria: معايرة تصميم الكوليسترات من أجل موازنة ضوء النهاري مع الأداء الحراري في سبيل رفع استدامة المباني الجامعية في سوريا - Abdalhamid M. Ghazi Almasri, Tarek M. Farouk Housam Al- Din (Journal of engineering sciences and information technology, 2020)
In a fully glazed building façade with solar inhibitors with holes (cholesters) (PSS), it is often used as an exterior casing in order to reduce energy consumption and solve other problems such as: transparency of vision. Moreover, the function of these cholesteres is not only to control the solar inhibitors entering the building, but also to control the provision of appropriate degrees of daylight, and thus we have created a balanced solution to the daytime lighting process. Nowadays, daylight simulation software applications enable us to apply scientific analyzes of daytime management in a vacuum when using cholesters (PSs). Regardless of that, current applications of sun simulation (such as: EnergyPlus) cannot deal with some engineering configurations directly, making the process of estimating the thermal factor of solar inhibitors with holes is not possible. This research provides a scientific method to achieve integrated analyzes of daytime lighting and energy consumption of voids using cholesteres during the design process on local university buildings, and such a scientific method provides us with daylight analyzes through (DIVA) and also provides thermal analyzes via EnergyPlus with DIVA / GRASSHOPPER / ARCHSIM The goal is to control the double performance of cholesters by controlling the intensity, arrangement, and shape of these perforations using the statistical method of vertical beams (DOA), and studying the simultaneous gain of daylight and the thermal efficacy of cholesters in order to provide an annual balanced and integrated solution. The (DOA) method is effective in reducing the number of simulations drawn from a mixture of the aforementioned variables and identifying the visual arrangements of these fluids. In comparison with an imperfect interface for a building located in the buildings of the University of Aleppo in Aleppo, these solar fluids with holes achieve an expectation of a decrease .The areas that are actually illuminated by daylight are (50%) and 55% less energy is needed in the building. Although this work uses the DOA method to improve the three design variables, it is possible in the future to increase these factors to include the thickness of the panels, the materials made from them and the slope of the panels.